Presurgical management trends and nasoalveolar molding usage for infants with cleft lip and palate in the capital of a developing country - Hadeel Adel Al-Lami; Dhelal Al-Rudainy; Harraa S Mohammed-Salih; Safa M Salman (Wolters Kluwer Medknow Publications, 2024)
BACKGROUNDS: Nasoalveolar molding (NAM) application is among presurgical management (PSM) techniques used for infants with cleft lip and palate (CLP). It helps to approximate the palatal cleft and to reshape the nasoalveolar complex prior to primary lip repair. This study aimed to explore types of PSM and the dental speciality provision for infants with CLP in Baghdad. The status of NAM usage and surgeons' perceptions toward NAM usage were assessed. MATERIALS AND METHODS: This is a cross-sectional paper-based questionnaire study that collected responses of surgeons perform primary lip and nose repair regarding PSM. The questionnaire was distributed amongst public and private hospitals in Baghdad. Twenty surgeons were enrolled (only those surgeons who perform primary repair for infants with CLP); two females and eighteen males. RESULTS: The majority of participants' responses suggested that the majority of infants with CLP were provided with baby feeding plates and lip straps. Six surgeons reported that a percentage of their patients who have been provided with NAM. PSM in Baghdad was mostly supplied by orthodontists and plastic surgeons, and the next most likely providers were prosthodontists. 82.35% of the surgeons found that primary surgical repair procedures were easier with NAM than for the other infants. The rest have not perceived any differences. CONCLUSIONS: Orthodontists, surgeons and prosthodontists were involved in providing PSM. Baby feeding plates and lip straps were the most common PSM in Baghdad, although NAM is not uncommon. Most surgeons believe that using NAM made surgical procedures easier and permitted the prediction of surgical outcomes.